PELAKSANAAN PROMOSI KEPARIWISATAAN SAMOSIR OLEH DINAS PARIWISATA, SENI DAN BUDAYA KABUPATEN SAMOSIR - Yosua Manullang; Andi M. Rifiyan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The purpose of this research was to investigate the implementationof Samosir tourism promotion conducted by department of tourism, arts andculture Samosir regency in increasing the number of tourists, obstaclesencountered and traveler feedback on the implementation of the promotionhas been done.This research uses theory of Yoeti (1996) to explanation on theimplementation of Samosir tourism promotion conducted by department oftourism, arts and culture regency Samosir using promotional mix aregrouped on the advertising, sales support and public relations.The method of this research is using qualitative descriptive analysismethod. Analysis on this research based on literature, observation anddirect interview with informan who consider able to provide informationrelating to problem examined.The number of tourist visits to Samosir increasing every year. It cannot be separated from efforts to implement the promotions by thedepartment of tourism, arts and culture Samosir regency and be thebarometer success of marketing strategy that has ben done.Key Words: Advertising, Public Relation, Promotion and Sales Support